Structure‐Induced Switching of the Band Gap, Charge Order, and Correlation Strength in Ternary Vanadium Oxide Bronzes. Issue 41 (27th June 2017) - Tolhurst, Thomas M.; Andrews, Justin L.; Leedahl, Brett; Marley, Peter M.; Banerjee, Sarbajit; Moewes, Alexander
Abstract: Recently, V2 O5 nanowires have been synthesized as several different polymorphs, and as correlated bronzes with cations intercalated between the layers of edge‐ and corner‐ sharing VO6 octahedra. Unlike extended crystals, which tend to be plagued by substantial local variations in stoichiometry, nanowires of correlated bronzes exhibit precise charge ordering, thereby giving rise to pronounced electron correlation effects. These developments have greatly broadened the scope of research, and promise applications in several frontier electronic devices that make use of novel computing vectors. Here a study is presented of δ‐Sr x V2 O5, expanded δ‐Sr x V2 O5, exfoliated δ‐Sr x V2 O5 and δ‐K x V2 O5 using a combination of synchrotron soft X‐ray spectroscopy and density functional theory calculations. The band gaps of each system are experimentally determined, and their calculated electronic structures are discussed from the perspective of the measured spectra. Band gaps ranging from 0.66 ± 0.20 to 2.32 ± 0.20 eV are found, and linked to the underlying structure of each material. This demonstrates that the band gap of V2 O5 can be tuned across a large portion of the range of greatest interest for device applications. The potential for metal–insulator transitions, tuneable electron correlations and charge ordering in these systems is discussed within the framework of our measurements and calculations, while highlighting the structure‐property relationships that underpin them. Abstract : Bronze medal : A series of vanadium oxide bronzes were studies with X‐ray absorptoion and emission spectroscopy. Experimental band gaps were determined and linked with the composition, demonstrating the ability to fine tune the V2 O5 band gap.